Preoperative inflammatory markers predict postoperative clinical outcomes in patients undergoing heart valve surgery: A large-sample retrospective study - Tian, Hongni; Jiang, Xuetao; Duan, Guangyou; Chen, Jie; Liu, Qi; Zhang, Yamei; Li, Shiqi; Bao, Xiaohang; Huang, He (Frontiers in Immunology, 2023)
Introduction: Preoperative inflammation affects the postoperative outcomes of patients undergoing heart valve surgery. This study aimed to explore the role and predictive effects of preoperative inflammation on primary outcomes after valvular cardiac surgery. Methods: This retrospective study utilized a medical recording system to screened 5075 patients who underwent heart valve surgery. Data on C-reactive protein (CRP) levels, erythrocyte sedimentation rate (ESR), and neutrophil-to-lymphocyte ratio (NLR) before heart valve surgery were collected based on the hospital medical system. Postoperative hepatic insufficiency, acute kidney injury, heart failure, and myocardial damage were assessed using blood examination indicators. Patients with and without prolonged mechanical ventilation, with and without an extended intensive care unit stay, with and without prolonged hospital stay, and with and without death within 30 days after surgery (which was considered as the primay outcome in this study) were compared. Group comparisons, receiver operating characteristic curve analyses (ROC), and logistic analyses were performed to determine the associations between preoperative inflammation and outcomes after heart valve surgery. Results: A total of 3249 patients were included in the analysis. Significant differences in CRP, ESR, and NLR were found between patients with or without postoperative adverse outcomes. ROC analysis showed that CRP >5 mg/L can effectively predict postoperative heart failure, and NLR >3.5 had a good predictive effect on all-cause mortality within 30 days after surgery. Patients with CRP >5 mg/L had a higher incidence of postoperative heart failure than other patients (20.7% vs. 12.6%, P<0.001), with a relative risk of 1.447 (95% confidence interval [95% confidence interval]: 1.155–1.814). Patients with NLR >3.5 had a higher incidence of death within 30 days after surgery (5.3% vs. 1.2%, P<0.001), with a relative risk of 3.236 (95% confidence interval: 1.773–5.906). Conclusion: Preoperative inflammation can affect postoperative outcomes in patients undergoing heart valve surgery. CRP >5 mg/L and NLR >3.5 can effectively predict postoperative heart failure and death within 30 days after surgery, respectively. Key words: valvular cardiac surgery; inflammation; postoperative outcomes; C-reactive protein; neutrophil-to-lymphocyte ratio.